POLLEN AND SEED MORPHOLOGY OF CRAMBE SPECIES OF TURKEY - A. S. Bülbül; B. Tarıkahya-Hacıoğlu; Y. Arslan; İ. Subaşı (Journal of Animal and Plant Sciences, 2017)
Our study includes 5 taxa out of 10 naturally growing taxa in Turkey: C. orientalis L. subsp. orientalis, C. orientalis L. subsp. sulphurea (Stapf ex O.E.Schulz) Prina, C. tataria Sebeök var. tataria, C. tataria Sebeök var. aspera (M.Bieb.) Boiss. and C. maritima L. The morphological characters of the pollen and seeds from the studied species of Crambe were given. Data obtained by light microscope, stereomicroscope and scanning electron microscope were explained and summarized in Tables. As a result of our study, there are high similarities among taxa in means of pollen grains. Pollen shape is suprolate to prolate-spheroidal. Crambe orientalis subsp. orientalis had the biggest pollen grains with 25.90 µm polar axis and 21.46 µm equatorial axis lengths, while Crambe orientalis subsp. sulphurea had the smallest-sized pollen grains with 22.75 µm polar axis and 21.07 µm equatorial axis lengths. Seeds are brown to dark brown, elliptic to orbicular, with reticulate surface. Crambe maritima had the biggest seeds with 2.8-4.1 x 2.3-3.4 mm, while Crambe orientalis subsp. sulphurea had the smallest-sized seeds with 2.0-2.6 x 1.7-2.4 mm. Since the group has stenopalynous pollens, our investigation supports the use of seed surface patterns as a diagnostic characteristic for species level instead of pollen morphology.
Keywords: Crambe; light microscopy; pollen grains; scanning electron microscopy; seed coat morphology